2003
DOI: 10.1046/j.1365-2958.2003.03882.x
|View full text |Cite
|
Sign up to set email alerts
|

A search for amino acid substitutions that universally activate response regulators

Abstract: SummaryTwo-component regulatory systems, typically composed of a sensor kinase to detect a stimulus and a response regulator to execute a response, are widely used by microorganisms for signal transduction. Response regulators exhibit a high degree of structural similarity and undergo analogous activating conformational changes upon phosphorylation. The activity of particular response regulators can be increased by specific amino acid substitutions, which either prolong the lifetime or mimic key features of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 97 publications
(127 reference statements)
3
63
1
1
Order By: Relevance
“…In both cases, the substitution results in constitutive activation, perhaps via a confomational change which mimics the conformation of the phosphorylated domain. It has been proposed that this substitution could represent a universal activating substitution for response regulators (Smith et al, 2004). This hypothesis may receive further support from the observation that the corresponding T903A mutation also has an activating effect in RcsC.…”
Section: Discussionmentioning
confidence: 64%
“…In both cases, the substitution results in constitutive activation, perhaps via a confomational change which mimics the conformation of the phosphorylated domain. It has been proposed that this substitution could represent a universal activating substitution for response regulators (Smith et al, 2004). This hypothesis may receive further support from the observation that the corresponding T903A mutation also has an activating effect in RcsC.…”
Section: Discussionmentioning
confidence: 64%
“…This suggested that these mutations might activate WspR to a high level; indeed, mutations within response regulators that either prolong the lifetime of the activated (phosphorylated) state or mimic key features of the phosphorylated state are well known (Smith et al 2004). Such mutations can have a number of specific effects; they can (1) increase the rate of autophosphorylation, (2) make the protein more resistant to dephosphorylation, or (3) mimic the conformational change ordinarily induced by phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…This led to predictions as to the means by which WspR might be activated, namely, by phosphorylation at Asp67. Indeed, mutations are known within the N-terminal domains of response regulators that cause constitutive activation of the output domain (Hoch and Silhavy 1995;Chamnongpol and Groisman 2000;Da Re et al 2002;Aldridge et al 2003;Siam and Marczynski 2003;Smith et al 2004). We therefore considered it plausible that mutations might arise within WspR to cause WS-that such mutations might cause constitutive activation of the GGDEF domain, overproduction of c-di-GMP, and concomitant overproduction of acetylated cellulose polymer.…”
mentioning
confidence: 99%
“…Analogous mutations have been demonstrated to confer constitutive function, at least partially, in several RRs, such as OmpR D55E , NtrC D54E , and CtrA D51E (28)(29)(30). It is also worth noting that mutation of the aspartate phosphorylation target to glutamate is only one type of mutation that can lead to constitutive activity of response regulators, but it is one for which the presumptive mechanism is most straightforward (33). In the case of RisA, D60E mutant protein is expected to provide a useful tool for in vitro studies of RisA-mediated gene regulation.…”
Section: Discussionmentioning
confidence: 99%